Komunikasi Simbolik Tradisi Sadranan Di Dusun Pantaran Desa Candisari Kecamatan Gladaksari Kabupaten Boyolali - Kusumawardani, Ria; Riyanto, Buddy; Sihabuddin, Sihabuddin (Solidaritas, 2024)
The Sadranan tradition in Pantaran Hamlet is a tradition carried out to honor the spirits of Pantaran ancestors which is carried out every year on the last Friday of the month of Suro. This study discusses how the symbolic communication of the Sadranan tradition in Pantaran Hamlet, Candisari Village, Gladaksari District, Boyolali Regency. This study aims to determine the process of symbolic communication and the meaning of the Sadranan tradition in Pantaran Hamlet, Candisari Village, Gladaksari District, Boyolali Regency. This study uses the symbolic interaction theory according to Herbert Blumer. Herbert Blumer's theory has three main premises, namely: 1) Humans act towards an object according to the meanings attached to them; 2) That meaning is the result of social interaction with others; and 3) Those meanings are considered perfect when the social interaction process is taking place. This study uses a qualitative research methodology to produce descriptive data in the form of both written and oral data obtained directly from the field. This research is supported by data in the form of interviews, observations and documentation. The data concluded also uses field data analysis techniques with the Miles and Huberman model. The results of the study show that there are various communication symbols in the Sadranan tradition including: tarub, pagar betek, Besik, Pilgrimage, Kirab, Kejawen Clothing, Royal Soldier Clothing, Incense and Frankincense, Lurup Cloth Covering the Tomb, Umbrella Tomb, Flower Sprinkles, Gunungan Hasil Bumi, Tahlilan, Kenduri, Berkatan, Topeng Ireng art, and finally Buka lawang or open house. The communication symbols in the Sadranan tradition are believed and believed to have deep meaning for the community so that the Sadranan tradition continues to be held and preserved by the community every year. Keywords: Symbolic Communication, Sadranan Tradition, Pantaran.